L1 Versus L2 Gender Agreement Processing: Reliance on Gender Assignment or Morphophonological Cue Matching? - Durand-López, Ezequiel M.; Iranzo, Vicente (Language and speech, 2025)
Studies exploring gender agreement processing in late bilinguals whose first language (L1) lacks the gender feature suggest that advanced second language (L2) learners can detect gender agreement violations in the L2. Importantly, these studies have mainly included gender canonical nouns (e.g., la silla, el libro ). However, the specific mechanisms L2 learners use while processing L2 gender agreement are unclear: Do learners rely on morphophonological cues (i.e., gender suffix) or on their gender assignment? In this study, English advanced L2 learners of Spanish and Spanish monolinguals completed a moving window task containing sentences with canonical and deceptive nouns engaged in noun–adjective gender (dis)agreement relations (e.g., casa antigua /* o, mano rosada /* o ). Results revealed that Spanish monolinguals and advanced L2 learners were sensitive to violations with canonical nouns. However, native speakers were significantly slower at computing gender disagreement than agreement with deceptive nouns, while advanced L2 learners exhibited the opposite processing pattern (i.e., they took longer to process gender agreement than disagreement with deceptive nouns). The findings suggest that native speakers seem to rely on their gender assignment, while L2 learners focus more on suffix matching patterns (i.e., if - o in the noun, - o in the adjective).